John Gregory's Writings on Medical Ethics and Philosophy of Medicine
XIII, 254 p.
Keywords: This volume introduces a new subseries of Philosophy and Medicine, Classics of Medical Ethics. The purpose of this new subseries is to bring out scholars' editions of major works in the history of medical ethics and philosophy of medicine. This new subseries will target for publication texts that are long out of print and difficult to access. Each volume will contain an introduction to the writings on medical ethics and philosophy of medicine produced by the original author. Each volume will also contain a guide to the primary and major secondary Hterature, to facilitate teaching and scholarship in bioethics, philosophy of medicine, and history of medicine. Texts will be presented in their origi nal style and will provide pagination of the original, so that citations can be made either to the original text or to the page numbers in these vol umes. Finally, each volume will be well indexed, again to facilitate teaching and research. Bioethics and philosophy of medicine - the former more so than the latter - have an insufficiently developed understanding of themselves as having a history. As a consequence, these fields lack the maturity that critical dialogue of the past with the present provides for other fields and disciplines of the humanities. To the extent that this problem is due to the fact that major primary historical sources are not readily available, this subseries will contribute to the further development and maturation of bioethics and philosophy of medicine as fields of the humanities.